A REMARK ABOUT THE ANALYSIS OF THE ILLOCUTIONARY ACT OF ASSERTION - GERGELY, P. Alpár (Studia Universitatis Babeș-Bolyai Philosophia, 2018)
A Remark about the Analysis of the Illocutionary Act of Assertion. The starting point of this article is the Searleian analysis of the illocutionary act of assertion. I try to sketch an alternative interpretation of the illocutionary act of assertion based on the arguments brought forward by John R. Searle, Paul Grice, Rom Harré, Robert Brandom. This possible interpretation might help us raise some questions about the Searleian interpretation.